Factors Influencing Acceptance to Use M-learning in Learning Arabic Language for Non-native Speakers in Saudi Universities - Dulaym Alotaibi, Faihan; Siraj, Saeedah; Said Ismail, Wail Muil Alhaj (Opción, 2019)
The acceptance of mobile learning apparatus in language learning in the Arab world in general and Saudi Arabia in particular is not widespread as expected, despite the several advantages the m-learning has offered to the rest of the world. Therefore, the present study intended to uncover the factors that significantly predict the intention to use mobile learning for learning Arabic to non-native speakers in Saudi Universities. Relevant model was developed by extending the unified theory of acceptance and use of technology (UTAUT) as well as incorporating three other factors namely; language interactivity (LI), system enjoyment (SE) as well as content quali- ty. Quantitative method based on cross-sectional survey design was emplo- yed for data collection from 460 students of teaching Arabic to non-native speakers’ programs in Saudi Universities. The tool used for analysis in this study was a Partial Least Squares (PLS) which was used to test the model empirically. It was found from the study that language interactivity (LI), system enjoyment (SE), performance expectancy (PE), facilitating condi- tions (FC), and expected effort (EE) are significant in relation (either directly or indirectly) to behavioural intention (BI) to use m-learning. The implication for future research development as well as the limitations of the findings are also discussed the paper.